The Phenomenon of Arabic Diglossia: A Linguistic Review and its Implications for Foreign Language Teaching : Fenomena Diglosia Arab: Tinjauan Linguistik dan Implikasinya bagi Pengajaran Bahasa Asing - Pahrul. R (Language Development Center, 2025)
Background: The phenomenon of Arabic diglossia, involving the use of Fusḥā and Ammiyah varieties, remains a challenge in foreign language teaching. The social functions and contexts of these varieties affect the effectiveness of Arabic language learning. Purpose: This study aims to examine the phenomenon of diglossia in Arabic from a linguistic perspective and explore its implications for teaching Arabic as a foreign language. Method: The study employs a qualitative approach through literature review in linguistics and language education. The analysis focuses on describing the diglossia phenomenon and strategies for managing it in Arabic language learning. Results and Discussion: The findings indicate that mastering both language varieties, Fusḥā and „Ammiyah, should be integrated into the curriculum to enable learners to use the language appropriately in social contexts. Learning that accommodates both varieties can enhance communicative competence and enrich the learning experience. Conclusions and Implications: The diglossia phenomenon requires a balanced approach in teaching Arabic, preserving the formal language while utilizing everyday speech. Practically, this implies developing inclusive and communicative teaching methods to support successful Arabic language learning as a foreign language.